2014
DOI: 10.14257/ijbsbt.2014.6.4.18
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Work Characteristics, Supervision, and Cultural Competence on Nurses’ Burnout

Abstract: This study examines the effects of work characteristics, superior supervision, and cultural competence on nurses' burnout. Controlling the effects of work characteristics and supervision, this study focuses on the effects of cultural competence influencing nurses' burnout. Participants in the study are nurses who are working at six small-and medium-size hospitals under 400 beds, which multicultural patients usually use, located in Seoul and Gyeonggi-do. The data were collected by the measure of cultural compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
6
1
1
Order By: Relevance
“…Our results suggest that high‐strain and high‐strain isolated jobs may negatively affect all dimensions of cross‐cultural competence in nursing personnel. These findings are in line with previous studies which have shown that lower levels of job control (Kaihlanen et al, ) and social support at work (Choi & Kim, ) as well as higher levels of job demands (Wesołowska et al, ) are associated with lower cross‐cultural competence among health and social care professionals. The results are also consistent with the conclusions of a recent literature review (Wazqar, Kerr, Regan, & Orchard, ) indicating that high‐strain jobs are associated with nurses’ poorer work performance that can reflect their level of competence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that high‐strain and high‐strain isolated jobs may negatively affect all dimensions of cross‐cultural competence in nursing personnel. These findings are in line with previous studies which have shown that lower levels of job control (Kaihlanen et al, ) and social support at work (Choi & Kim, ) as well as higher levels of job demands (Wesołowska et al, ) are associated with lower cross‐cultural competence among health and social care professionals. The results are also consistent with the conclusions of a recent literature review (Wazqar, Kerr, Regan, & Orchard, ) indicating that high‐strain jobs are associated with nurses’ poorer work performance that can reflect their level of competence.…”
Section: Discussionsupporting
confidence: 92%
“…The aim of the present study was to investigate whether psychosocial work characteristics, such as high‐strain jobs, high‐strain isolated jobs, active jobs, and active collective jobs, are associated with cross‐cultural competence (empathy, skills, positive attitudes, and motivation), and whether there are differences between native Finnish and foreign‐born registered nurses (RNs) in these plausible associations. Previous cross‐sectional studies (Choi & Kim, ; Kaihlanen, Hietapakka, Aalto, Lehtoaro, & Heponiemi, ; Wesołowska et al, ) have shown that cross‐cultural competence is associated negatively with job demands and positively with job control and social support at work among health and social care professionals. These psychosocial work characteristics, however, have not been studied together, leaving their interactive effect on cross‐cultural competence unclear.…”
Section: Introductionmentioning
confidence: 97%
“…In a review, Williamson and Harrison () argue that the focus should be on cognitive aspects of culture and health professionals' education about the culture of special groups. Choi and Kim () found that cultural competence is a significant factor affecting nurses' burnout. The present study revealed that decreasing stress plays an important role for increasing nurses' cultural sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Beban kerja adalah kemampuan tubuh pekerja menerima pekerjaan (Choi, 2014). Setiap beban kerja yang diterima seseorang harus sesuai dan seimbang terhadap kemampuan fisik maupun psikologis pekerja yang menerima beban kerja tersebut (Manuho, 2015).…”
Section: Beban Kerjaunclassified